KONSEP KEBAHAGIAAN PERSPEKTIF PSIKOLOGI DAN AL-QUR’AN
The concept of happiness described in this paper is based on two perspectives, namely psychology and the al-Qur’an, then a correlation between the two results in a comprehensive understanding which is continuous. So that the concept of happiness in the Koran does not contradict, it even becomes the basis for the development of the concept of happiness in sustainable psychological theories. So that the concept of happiness in the Koran is not contradictory and even becomes the basis for the development of the concept of happiness in psychological theories. This is in line with the character so that people can achieve al-fala>h